DESIGNING SPEAKING MATERIAL SAMPLES BASED ON COMMUNICATIVE LANGUAGE TEACHING - Hertika, Irva; Apriliaswati, Rahayu; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: Penelitian ini bertujuan untuk merancang materi untuk speaking berdasarkan Communicative Language Teaching untuk siswa kelas VIII semester 2 di SMP Negeri 1 Pontianak. Materi tersebut dirancang untuk menyediakan materi speaking alternatif berdasarkan CLT. Sebelum merancang materi speaking, penulis melakukan survey terlebih dahulu. Setelah itu penulis merancang materi speaking yang memiliki prinsip-prinsip dari CLT, prinsip-prinsip merancang materi, aspek-aspek rancangan materi, dan prinsip dari pengembangan materi speaking. Berdasarkan hasil interview siswa dan guru, didapatkan bahwa materi yang dirancang oleh penulis telah memenuhi prinsip-prinsip CLT. Kata kunci: Communicative Language Teaching, Design, Speaking Abstract: This research was aimed at designing speaking material samples based on Communicative Language Teaching for the second semester of eight grade students of SMP Negeri 1 Pontianak. The materials designed in order to provide the alternative speaking materials based on CLT. Before designing the speaking materials, the writer did a preliminary study. After that, the writer designed speaking material samples which fulfilled the principles of CLT. The speaking materials designed had fulfilled the principles of CLT, principles of material design, aspects of material design and principles of speaking material development. Based on the students and teachers interview, the result showed that the materials designed by the writer had fulfilled the principles of CLT. Key words: Communicative Language Teaching, Design, Speaking